Managing Cytospora canker in Colorado peach orchards: canopy spray efficacy and implementation strategies - Greenberger, Sal, author (Colorado State University. Libraries, 2024)
This presentation, delivered as part of a Master's thesis defense at Colorado State University, summarizes the methodologies, results, and key findings of research on management of Cytospora canker in Colorado peach orchards. The research evaluates the efficacy of fungicidal canopy sprays applied with air-blast sprayers against Cytospora plurivora and explores best practices for their use in orchard management.
Department of Agricultural Biology, Colorado State University. Advisor: Jane E. Stewart, Committee Members: Bradley W. Tonnessen, Amy Charkowski, and Mark Uchanski.
Keywords: Cytospora canker; Cytospora plurivora; Leucostoma; canopy sprays; peach; Colorado; air-blast sprayer; fungicides; disease management; mycology; plant pathology